Cerebrospinal Fluid Leak After Septoplasty in Crouzon Syndrome - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Crouzon syndrome presents with craniofacial deformities due to early fusion of cranial sutures. Deviation of the nasal septum could be seen clinically in Crouzon syndrome. Cerebrospinal fluid leaks (CSF) after septoplasty are extremely rare and typically present with simple rhinorrhea, meningitis, and pneumocephalus. Herein, we report an adult patient with Crouzon syndrome who experienced CSF complication after septoplasty surgery.
Keywords: cerebrospinal fluid leak; crouzon syndrome; rongeur forceps; septoplasty